1993
DOI: 10.1093/tropej/39.1.4
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Technology and Temperature Control on a Neonatal Unit in Kathmandu, Nepal

Abstract: An assessment of the incubators in use at the Kathmandu Maternity Hospital neonatal unit was undertaken; this was followed by a prospective survey of neonatal temperatures on the unit. In the incubator assessment 11 studies were carried out in five incubators. Three of the thermostats in the five incubators did not work at all and those in the other two incubators were more than 3 degrees C inaccurate. All the incubator thermometers gave recordings less than the actual temperature (with a range of error: 1.3-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Many studies revealed increased incidence (11-85%) of hypothermia among hospital and home-born newborn in South Asia, including Bangladesh, India, Pakistan, Bhutan and Nepal, as well as in developing countries with tropical climate 12 . For example, in Nepal, 85% of newborns in a maternity hospital had a temperature <36 0 C within 2 h of birth 13 . In Ethiopia, Zambia and Zimbabwe, one-half to two-thirds of newborns evaluated were hypothermic 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies revealed increased incidence (11-85%) of hypothermia among hospital and home-born newborn in South Asia, including Bangladesh, India, Pakistan, Bhutan and Nepal, as well as in developing countries with tropical climate 12 . For example, in Nepal, 85% of newborns in a maternity hospital had a temperature <36 0 C within 2 h of birth 13 . In Ethiopia, Zambia and Zimbabwe, one-half to two-thirds of newborns evaluated were hypothermic 12 .…”
Section: Discussionmentioning
confidence: 99%
“…3,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Uniform adoption and application of the standard WHO definition is fundamental to coordinated advancements in detection and management, but hypothermia continues to be variably defined, leading to under-recognition and under-reporting, and inadvertent denial of care to those who are misclassified but in need of care.…”
Section: Definitionmentioning
confidence: 99%
“…For example, in Nepal, 85% of newborns in a maternity hospital had a temperature <36 1C within 2 h of birth. 16 In Ethiopia, 56 Zambia 57 and Zimbabwe, 17 one-half to two-thirds of newborns evaluated were hypothermic. The incidence of primary hypothermiaFan independent morbidity that presents as a result of cold stressFis high immediately following birth in hospital settings.…”
Section: Pathophysiology Of Neonatal Hypothermiamentioning
confidence: 99%
See 1 more Smart Citation
“…In our review, case fatality rates (CFR) for newborn hypothermia globally range from 8.5% to 52% [21,26,34,59,60]. A study from India that included only hypothermic babies specifically investigated morbidities and mortalities and found CFRs that ranged from 39.3% for mild hypothermia to 80% for severe hypothermia.…”
Section: Associations Of Hypothermia With Newborn Morbidity and Mortamentioning
confidence: 99%